Food Innovation as a Means of Developing Healthier and More Sustainable Foods - Rabadán, Adrián; Bernabéu, Rodolfo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The current demand for healthy and sustainable foods has encouraged the development of new alternatives, even in traditional products. Improved foods may be produced by reducing the amount of some ingredients, adding new ones, or replacing traditionally used ingredients for others. By reformulating their products, manufacturers can offer healthier choices for an ever-growing number of consumers interested in maintaining a balanced diet. In addition, market demand for more sustainable foods contributes to a lower environmental impact in their production. In this regard, current areas of interest include the production of foods using a lower amount of inputs, as well as the utilization of food by-products to improve the amount and quality of available foods. Another aspect to be considered is that not all consumers are willing to eat foods produced with new ingredients or novel technologies. Hence, the development of innovations in food products should take into account the influence of the so-called consumer food neophobia. For this reason, papers dealing with the consumer acceptance of these food innovations are also welcome. Thus, the aim of this Special Issue of Foods is to provide documents focused on the production of healthier and more sustainable foods by using novel ingredients, food by-products, or new production processes.